MO941: Novel Peripheral Molecular Markers Predict Premature Graft Loss: Lessons Learned from Operational Tolerance Assessment. (3rd May 2022) - Hruba, Petra; Klema, Jiri; Wu Le, Anh; Girmanova, Eva; Mrazova, Petra; Massart, Annick; Abramowitz, Daniel; Abramowicz, Marc; Viklicky, Ondrej
Abstract: BACKGROUND AND AIMS: TOMOGRAM, a European multicenter study, recently identified a new cohort of kidney transplant recipients (KTR) with operational tolerance (OT) with the aim to identify new transcriptomic signatures of OT. METHOD: RNA sequencing of peripheral blood was evaluated in 15 OT KTR identified by TOMOGRAM, 23 stable KTR (≥15 years, STA), 14 KTR with transplant glomerulopathy (≥1 year, CR), 14 CyA-treated primary GN patients and 14 healthy controls (HC). The ability to discriminate OT from others was analyzed using three classifiers (GLMNET, voomNSC and SVM-RFE) with 10-fold cross-validation and visualized by principal component analysis (PCA) of molecular archetypes. RESULTS: Peripheral blood transcriptome of OT patients is similar to the STA group (AUC < 0.6) and different from the CR group (AUC > 0.8). Also, in PCA of molecular archetypes, direction of correlation suggested similarity between STA and OT and their anti-correlation to CR (Figure 1). Top 10 transcripts differentiated OT from CR were assessed in prospective independent cohort ( n  = 396) to predict premature graft loss. Multivariable Cox regression model based on the expression of 5 of those transcripts at 3 time-points was associated with graft loss at 3 years with an AUC = 0.815. CONCLUSION: Identification of the OT peripheral molecular signature among stable KTR is not feasible. Instead, novel peripheral molecular markers associated with premature graft loss were identified.